Understanding Antenatal Care Utilization Among Pregnant Women In Indonesia : A Literature Review - Kartika Aprilia (Universitas Malahayati, 2026)
ABSTRACT Antenatal care (ANC) services are one of the efforts to reduce Maternal Mortality Rate (MMR) and Infant Mortality Rate (IMR). However, the coverage of ANC visits has not yet reached the target, indicating the presence of factors that influence the utilization of ANC services. The objective of this study is to identify the factors influencing the use of antenatal services among pregnant women in Indonesia. This study uses a literature review design with journal articles as references. Articles were searched using the keywords